Near-infrared light-triggered β-NaYF4:Yb, Tm, Gd@MIL-100(Fe) nanomaterials for antibacterial applications. (18th February 2022) - Song, Jie; Sun, Leilei; Geng, Hongchao; Tan, Wenlong; Zhen, Deshuai; Cai, Qingyun
Abstract : By inducing a photo-Fenton reaction under 980 nm light irradiation, β-NaYF4 :Yb, Tm, Gd@MIL-100(Fe) could generate abundant ROS for antibacterial applications. Abstract : β-Phase NaYF4 :Yb, Tm, Gd up-conversion nanorods (UCNRs) with high uniformity were synthesized by a solvothermal method. The optimal fluorescence intensity of UCNRs was explored. After further modification with Materials of Institute Lavoisier-100(Fe) (MIL-100(Fe)) by the layer-by-layer self-assembly method, near-infrared light-triggered UCNR@MIL-100(Fe) nanomaterials with excellent antibacterial performances were constructed. A core–shell structure was constructed and confirmed by transmission electron microscopy (TEM). Reactive oxidizing species (ROS) detection indicated that the nanomaterials owned good photodynamic efficacy. The antibacterial experiments showed that the nanomaterials with 980 nm light irradiation and hydrogen peroxide (H2 O2 ) had good antibacterial activity against Gram-negative and Gram-positive bacteria. Under 980 nm laser excitation, UCNRs generated ultraviolet and visible light to activate MIL-100(Fe) and induced a photo-Fenton reaction, which further produced oxygen species for antibacterial applications.